2023
DOI: 10.3389/fpubh.2023.1136178
|View full text |Cite
|
Sign up to set email alerts
|

Does the disclosure of medical insurance information affect patients’ willingness to adopt the diagnosis related groups system

Zhenni Shi,
Qilin Zhang,
Xiaofeng Wang

Abstract: IntroductionMedical insurance information disclosure is not only a direct way for the public to understand and master social insurance information and resource use benefits, but also an important way for the public to participate in medical service governance and supervision. Some studies have shown that information disclosure can significantly reduce the risk perception of user groups, strengthen their trust and reduce the negative impact of information asymmetry.MethodsBased on risk perception and trust perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Several studies have indicated that the disclosure of government information can increase citizen trust [25], while the disclosure of enterprise information can enhance market trust [25,26]. Additionally, the disclosure of medical insurance information has been found to improve patient trust [22,27], and the disclosure of product information can boost consumer trust [28,29]. A multi-dimensional model of e-commerce trust categorizes consumers' trust in online merchants into three dimensions: competence trust, benevolence trust, and integrity trust [30].…”
Section: Stimulus-organism-response Modelmentioning
confidence: 99%
“…Several studies have indicated that the disclosure of government information can increase citizen trust [25], while the disclosure of enterprise information can enhance market trust [25,26]. Additionally, the disclosure of medical insurance information has been found to improve patient trust [22,27], and the disclosure of product information can boost consumer trust [28,29]. A multi-dimensional model of e-commerce trust categorizes consumers' trust in online merchants into three dimensions: competence trust, benevolence trust, and integrity trust [30].…”
Section: Stimulus-organism-response Modelmentioning
confidence: 99%
“…Therefore, sellers should use extrinsic cues signals to convey product quality information to consumers. Failure to provide truthful disclosure of information in the health care system harms enhancing patient trust and exacerbates their perceived risk (Shi et al, 2023). Luce and Raiffa highlighted that the problem of choice under uncertainty may be addressed by increasing the quantity of information accessible to the decision-maker (Luce and Raiffa, 1957).…”
Section: The Mediating Role Of Perceived Uncertainty On Information A...mentioning
confidence: 99%
“…Therefore, sellers should use extrinsic cues signals to convey product quality information to consumers. Failure to provide truthful disclosure of information in the health care system harms enhancing patient trust and exacerbates their perceived risk (Shi et al. , 2023).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%